2010
DOI: 10.1007/s00222-010-0247-x
|View full text |Cite
|
Sign up to set email alerts
|

The early evolution of the H-free process

Abstract: The H-free process, for some fixed graph H, is the random graph process defined by starting with an empty graph on n vertices and then adding edges one at a time, chosen uniformly at random subject to the constraint that no H subgraph is formed. Let G be the random maximal H-free graph obtained at the end of the process. When H is strictly 2-balanced, we show that for some c>0, with high probability as $n \to \infty$, the minimum degree in G is at least $cn^{1-(v_H-2)/(e_H-1)}(\log n)^{1/(e_H-1)}$. This gives … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
393
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(405 citation statements)
references
References 26 publications
11
393
0
1
Order By: Relevance
“…Let K 3 4 \ e denote the 3-uniform hypergraph on four vertices, obtained by removing one edge from K 3 4 . A simple argument of Erdős and Hajnal [12] implies r(K 3 4 \ e, K 3 n ) < (n!)…”
Section: Ramsey Numbers For K-half-graphs Versus Cliquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Let K 3 4 \ e denote the 3-uniform hypergraph on four vertices, obtained by removing one edge from K 3 4 . A simple argument of Erdős and Hajnal [12] implies r(K 3 4 \ e, K 3 n ) < (n!)…”
Section: Ramsey Numbers For K-half-graphs Versus Cliquesmentioning
confidence: 99%
“…Here we study the off-diagonal Ramsey number, that is, r k (s, n) with k, s fixed and n tending to infinity. It is known that for fixed s ≥ k + 1, r 2 (s, n) grows polynomially in n [1, 2,3] and r 3 (s, n) grows exponentially in a power of n [6]. In 1972, Erdős and Hajnal [12] raised the question of determining the correct tower growth rate for r k (s, n).…”
Section: Introductionmentioning
confidence: 99%
“…Then, by applying the induction hypothesis on (T , E) and (T i , E) for each i and by (6), there exists a subset P ⊂ T such that P 3 ∩ E = ∅ and |P | ≥ e α (r+s) (log N α 2 /18 ) e α (r+s) (log N α )…”
Section: The Off-diagonal Casementioning
confidence: 99%
“…The off-diagonal Ramsey numbers, i.e., R k (s, n) with s fixed and n tending to infinity, have been intensively studied. For example, it is known [1,5,6,20] that R 2 (3, n) = Θ(n 2 / log n) and, for fixed s > 3,…”
Section: Introductionmentioning
confidence: 99%
“…For example, Erdős [8] conjectured that r(C 4 , K m ) = O(m 2− ) for some absolute constant > 0, and this conjecture is still open. The current best upper bound is an unpublished result of Szemerédi which was reproved by Caro, Rousseau, and Zhang [7] where they showed that r(C 4 , K m ) = O(m 2 / log 2 m) and the current best lower bound is Ω(m 3/2 / log m) by Bohman and Keevash [5]. In sharp contrast, for three colors Alon and Rödl [2] determined r(C 4 , C 4 , K m ) up to a poly-log factor and found the order of magnitude of r k (C 4 ; K m ) for k ≥ 3.…”
Section: Introductionmentioning
confidence: 97%